A novel approach for synthesis of poly(norbornene)‐co‐poly(styrene) block copolymers via metathesis polymerization and free‐radical polymerization. Issue 39 (9th September 2018) - Miao, Pengcheng; Lin, Shaohui; Rempel, Garry L.; Pan, Qinmin
Abstract: It is successfully realized that block copolymers are synthesized via metathesis polymerization followed by free‐radical polymerization. This method is performed using styrene (St) and norbornene, one block is synthesized using the Grubbs second generation catalyst in the presence of chain transfer agents, and the subsequent polymerization of St is initiated by azo compounds to complete the additional blocks in the copolymers. The use of free‐radical polymerization instead of controlled radical polymerization or ionic polymerization can be potentially superior for industrialization. As a result, the molecular weights of the block copolymers ranging from 10.4 to 54.3 kDa and polydispersity indices ranging from 1.30 to 1.91 are obtained. In principle, this new method can be potentially useful to prepare a broad range of block copolymers with cyclic olefin groups in the main chains, which may be used in some particular applications. Abstract : Metathesis and functionalization using azo compounds followed by free‐radical polymerization to form block copolymers.